Bioinspired Oxidative Cleavage of Aliphatic C–C Bonds Utilizing Aerial Oxygen by Nickel Acireductone Dioxygenase Mimics. Issue 16 (22nd January 2019) - Raje, Sakthi; Mani, Kalaikodikumaran; Kandasamy, Parameswaran; Butcher, Ray J.; Angamuthu, Raja
Abstract : Bioinspired oxidative cleavage of aliphatic C–C bonds of the acireductone model substrate 2‐hydroxy‐3‐oxo‐1, 3‐diphenylprop‐1‐en‐1‐olate, bound to two paramagnetic nickel(II) complexes that are mimics for the nickel containing acireductone dioxygenase, has been achieved utilizing aerial oxygen under ambient conditions. Abstract : Nickel Acireductone Dioxygenase Mimic: Bioinspired oxidative cleavage of aliphatic C–C bonds of the acireductone model substrate, 2‐hydroxy‐3‐oxo‐1, 3‐diphenylprop‐1‐en‐1‐olate, bound to two paramagnetic nickel(II) complexes that are mimics for the nickel containing acireductone dioxygenase, has been achieved utilizing aerial oxygen under ambient conditions.